The Effect of Earnings Management, Profitability, Leverage and Transfer Pricing on Tax Avoidance in the P3 sector” (Plantation, Forestry and Mining) Empirical Study - Imelda Imelda; Selamet Riyadi; Setyani Dwi Lestari (International Journal of Social Service and Research, 2022)
This study aims to analyze the effect of Earnings Management, Profitability, Leverage and Transfer Pricing on tax avoidance. This research was conducted on companies engaged in the P3 sector (Plantation, Forestry and Mining) listed on the IDX in 2017 to 2021. The type of research used in this study was descriptive qualitative, using 22 samples of companies engaged in the P3 sector with a non- probability method. sampling is a purposive sampling technique. The analysis technique used in this research is panel data regression analysis. The results of the analysis show that Earnings Management, Profitability and Transfer Pricing have no significant effect on tax avoidance by companies operating in the P3 sector while leverage has a significant effect on tax avoidance of companies operating in the P3 sector.